Early Use of Handgrip Exercise Associated with Dobutamine Stress Echocardiography in Women - Lindner,Isabela de Andrade (2021)
Abstract Background Coronary artery disease (CAD) is an important cause of morbidity and mortality in women and requires early diagnosis for defining the appropriate treatment. Objective To identify the positive predictive value (PPV) and safety of the early use of handgrip exercise in pharmacological stress echocardiography using dobutamine (early-ECHO) in women. Methods Positive ischemic early-ECHO records from 111 women were evaluated from January 2012 to March 2018. Subsequently, the hospital medical records were verified to locate patients who underwent conventional coronary angiography (CCA), and we analyzed the medical conduct adopted for these patients. Statistical analyses were performed using SPSS employing one-way analysis of variance (ANOVA), Fisher’s exact test, or Pearson’s chi-square test. The level of statistical significance was set at p < 0.05 for all analyses. Results Four patients (4.4%) presented serious complications during the examination. Out of 90 patients who underwent CCA, 71 (78.9%) had CAD. Among these 71 patients, 58 (81.7%) had severe lesions and 13 (18.3%) presented moderate CAD. Moreover, CCA did not demonstrate relevant coronary lesions in 19 of the 90 patients (21.1%). Among patients with severe CAD, 16 (27.6%) underwent myocardial revascularization surgery; 34 (58.6%) underwent percutaneous coronary angioplasty; and 08 (13.7%) had their clinical treatments intensified. The PPV for early-ECHO was 78.9%. Conclusions Early-ECHO showed a high PPV for diagnosing myocardial ischemia in women. It presented a low complication rate and provided rapid disease identification, allowing the early treatment of injuries and potentially preventing CAD complications.